Reaching the Unreachable: UT Bandarlampung's Marketing Communication Strategy to Increase the Number of New Students - Novaria, Sarah Ayu Putri; Bintarti, Arifah (Universitas Syiah Kuala, 2025)
The purpose of this research is to investigate the marketing communication strategy employed by the Open University of Bandarlampung to increase the number of new students. This research is considered important due to the increase in the number of new UT Bandarlampung students over the past two years, during which the trend has remained stable. UT Bandarlampung managed to increase the number of new students by 214.39% compared to the 2023 registration period, and 58.47% compared to the previous year. The success of UT Bandarlampung in increasing the number of new students is inseparable from the marketing communication strategy that has been carried out. This research was conducted with descriptive qualitative research methods. Data collection techniques involve semi-structured interviews with informants selected through purposive sampling techniques. In this study, it is known that UT Bandarlampung carries out a marketing communication strategy with the Integrated Marketing Communication (IMC) Mix. In this mix, UT Bandarlampung's marketing activities are dominated by advertising through social media. Data leads from these advertisements are then followed up with personal selling via WhatsApp. This research is expected to be useful for UT Bandarlampung to optimize marketing communication strategies in an effort to increase the number of students. This research can also serve as a contribution of thought for other UT regions in applying marketing communication strategies.